Analysis of the Power Dissipation of a Linearly Graded Profile in the Drift Region of a 6H-SiC DIMOSFET - Kumar, Vinit (My University, 2008)
Inautomotive,aerospaceandenergyproductionindustries,thesemiconductorbasedelectronicdevicesthatcanfunctionatambienttemperatureshigherthan150oCwithoutexternalcoolingsystemcouldgreatybenefitavarietyofapplication.Apracticaloperationofsiliconpowerdevicesatambienttemperatureabove200Cappearsproblematic,asself-heatingathigherpowerlevelsresultsinhighinternaljunctiontemperaturesandleakages.Thus,mostelectronicsubsystemsthatsimultaneouslyrequirehigh-temperatureandhighpoweroperationwillnecessarilyberealizedusingwidebandgapdevices. TheSiliconcarbide(SiC)iswidebandgapsemiconductormaterialthatreplacesSimaterialveryquicklyinthesemiconductorindustrybecauseofitssuperiorintrinsicpropetieslikelowerintrinsiccarrierconcentration(10–35ordersofmagnitude),higherelectricbreakdownfield(4–20times),higherthermalconductivity(3–13times),largersaturatedelectrondriftvelocity(2–2.5times);whichissuitableforfastdeviceoperationwithhighvoltageandhighswitchingfrequency. Thepresentworkaimsatthedesignofhighbreakdownvoltage8kV6H-SiCDoubleimplantedmetal-oxidesemiconductorfield-effecttransistor(DIMOSFET)withuniformlyandlinearlygradeddopingprofileofdriftregion.Inlinearlygradeddopingprofile,itisfoundthattheheightofthedriftregion(h)decreases(148.17μmto119.61μm),whichreducesthespecificonresistanceRon,sp.HereRon,sp(specificonresistance)equaltoRD(Specificonresistanceofthedriftregion)forhighbreakdownvoltages.Andthepowerdissipation(PD)with8kVbreakdownvoltage(Vb)decreasestothevalueof29.56Wfrom43.88Watafixedforwardcurrentdensity(Jf=1000A/cm2)andeffectivedopinglevel(Nd=3.91x1014cm-3).Thepercentagepowersavedinlinearlygradeddopingprofileisabout32.64%ascomparedtotheuniformlydopedprofile,butitdecreaseswithfurtherincreaseintheeffectivedopinglevel.
M.Tech. (VLSI Design and CAD)
Keywords: 6H SiC; Graded Doping Profile; DMOS; DIMOSFET